2021
DOI: 10.3390/v13081593
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 Derived Small RNAs and Changes in Circulating Small RNAs Associated with COVID-19

Abstract: Cleavage of double-stranded RNA is described as an evolutionary conserved host defense mechanism against viral infection. Small RNAs are the product and triggers of post transcriptional gene silencing events. Up until now, the relevance of this mechanism for SARS-CoV-2-directed immune responses remains elusive. Herein, we used high throughput sequencing to profile the plasma of active and convalescent COVID-19 patients for the presence of small circulating RNAs. The existence of SARS-CoV-2 derived small RNAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 73 publications
3
35
1
Order By: Relevance
“…Upon abstract collection, 44 research papers (23 in silico [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and 21 experimental studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]) met the inclusion criteria and were used for downstream analysis. The entire workflow of the current study is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Upon abstract collection, 44 research papers (23 in silico [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] and 21 experimental studies [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]) met the inclusion criteria and were used for downstream analysis. The entire workflow of the current study is depicted in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Another investigation in which plasma samples from COVID-19 patients were examined using high throughput sequencing approach to detect small circulating RNAs buttressed that four small virus-derived RNAs similar in size to human miRNAs are linked with COVID-19 symptoms and ageusia. These virus-derived tiny RNAs might represent promising biomarkers since they present abundantly even in recovered COVID-19 patients ( Grehl et al, 2021 ). In this same study, 20 miRNAs displayed lower abundance in severe cases of COVID-19, while 11 miRNAs were upregulated.…”
Section: Biomarkers and Future Therapeuticsmentioning
confidence: 99%
“…In this same study, 20 miRNAs displayed lower abundance in severe cases of COVID-19, while 11 miRNAs were upregulated. Among these differentially expressed miRNAs, hsa-miR-320a-3p, hsa-miR-629-5p, hsa-miR-29a-3p, hsa-miR-342-3p, hsa-miR-185-5p, and hsa-miR-4516 were the most representative ones because of their possible association with severe states of COVID-19 and their potential application in molecular diagnostics ( Grehl et al, 2021 ).…”
Section: Biomarkers and Future Therapeuticsmentioning
confidence: 99%
“…It has been reported that the N protein of SARS-CoV-2 may act as a viral suppressor of RNAi [9]. Several publications have reported results of small RNAs and SARS-CoV-2-infection related studies, and potential vsmRNAs have been identified [10][11][12][13][14][15][16][17][18][19]. However, a consensus has not been reached yet.…”
Section: Introductionmentioning
confidence: 99%